Clinical and economic burden of head and neck cancer: a nationwide retrospective cohort study from France - Schernberg A; Sagaon-Teyssier L; Schwarzinger M (Dove Medical Press, 2019)
Antoine Schernberg,1 Luis Sagaon-Teyssier,2,3 Michaël Schwarzinger,3,4 On behalf of the EPICORL Study Group1Department of Radiation Oncology, Hôpital Tenon, AP-HP, Paris, France; 2Aix Marseille Univ, INSERM, IRD, SESSTIM, Marseille, France; 3Translational Health Economics Network (THEN), Paris, France; 4Infection Antimicrobials Modeling & Evolution (IAME), UMR 1137, Institut National de la Santé et de la Recherche Médicale (INSERM), Université Paris Diderot, Sorbonne Paris Cité, Paris, FranceObjectives: To evaluate the clinical and economic burden of head and neck squamous cell carcinoma (HNSCC) in France.Methods: All 53,255 incident adult patients discharged with a first diagnosis of HNSCC in 2010–2012 were identified from the 2008–2013 French National Hospital Discharge (PMSI) database. We conducted a retrospective longitudinal analysis of prognosis and direct costs attributable to HNSCC.Results: Direct medical costs attributable to HNSCC care amounted to 665 million euros in 2012 in France. The majority (62%) of incident patients were 64 years old or less at HNSCC diagnosis and incurred 1.3-fold higher mean direct costs as compared to elderly patients (41,909 vs 32,221 euros over 3 years, respectively; p<0.001). HNSCC stage at initial treatment was the major driver of mean (SD) direct costs over 3 years (p<0.001): 19,819 (23,150) euros in 31% patients diagnosed at early stage; 46,791 (34,841) euros in 60% patients diagnosed at locally advanced stage; and 43,377 (33,953) euros in 9% patients diagnosed with distant metastasis. About half patients died over 3 years at a median (IQR) age of 63 (56–75) years resulting in 10.9 years-of-life lost on average per incident patient.Conclusion: The present study suggests that the clinical and economic burden of HNSCC is substantial in France.Keywords: head and neck squamous cell carcinoma, prognosis, costs, burden of disease, National Hospital discharge database